DYNAMICS OF SOME SOCIO-ECONOMIC CHANGES IN KAZAKHSTAN FAMILIES (BY RESULTS OF SOCIOLOGICAL RESEARCH) - Shabdenova, Aizhan (Farabi Journal of Social Sciences, 2021)
The article presents a sociological analysis of various aspects of family structure in Kazakhstan. The dynamics of changes in the structures of families in the transformation period is shown. It is based on data from international research projects supported by grants from the European Union. The designated projects are aimed at studying the life of the population of the countries of the former Union of Soviet Socialist Republics (USSR). These are large-scale sociological surveys with a representative sample, the results of which are still used to write scientific articles, since they reflect the social processes of countries in a period of transformation, accompanied by changes in social ties and institutions. The results showed that over the past ten years there have been quite noticeable changes, both in marital status and in the structure of families in Kazakhstan, both in the urban and in the rural. One of the main changes is a decrease in the proportion of those who were married, both among men and among women; first, this change was due to the increase in those who never married. The structure of Kazakh families has also changed; the share of extended families has increased. In general, residents of Kazakhstan are positive about the prospects for changing the welfare of their families. Key words: family, families of the population of Kazakhstan, transformation period, family changes, social structure.